1962
DOI: 10.1002/ardp.19622951103
|View full text |Cite
|
Sign up to set email alerts
|

Notiz über eine Ätherspaltung mit Lithiumaluminiumhydrid

Abstract: Robinson und Mirzal) haben Narkotin (I, R = OCH,) mit Lithiumaluminiumhydrid zu dem entsprechenden Diol (11, R = OCH,) reduziert, fur das wir den Namen Narkotinogen-diol fur geeignet halten. I n der Publikation sind keine Versuchsbedingungen, angegeben. \/ \Da sich Narkotinbase schwer in Ather, aber leicht in Tetrahydrofuran lost, reduzieren wir vergleichsweise in beiden Losungsmitteln. Bei der Aufarbeitung stellten wir fest, daB bei der Verwendung von Tetrahydrofuran im Gegensatz zur atherischen Losung nicht … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1963
1963
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Farm. 24 (1-2), [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] (1963); C.A. 60, 39490 (1964).…”
Section: Pyridinesmentioning
confidence: 99%
“…Farm. 24 (1-2), [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] (1963); C.A. 60, 39490 (1964).…”
Section: Pyridinesmentioning
confidence: 99%
“…Two groups (101,150) have observed that reduction occurs as expected, to the corresponding diol LXXX (R = CH3). Another group has reported that in tetrahydrofuran, partial demethylation occurs simultaneously, leading to the phenol LXXX (R = H), itself the LAH reduction product of narcotoline (8-demethylnarcotine) (6). The reduction is inhibited by pyridine (100).…”
Section: LXXXImentioning
confidence: 99%